Native Bicuspid Pulmonary Valve in D‐Loop Transposition of the Great Arteries: Outcomes of the Neo‐Aortic Valve Function and Root Dilation After Arterial Switch Operation - Margaret Irwin (Wiley, 2021)
Background Neo‐aortic root dilation and neo‐aortic regurgitation (AR) are common after arterial switch operation for D‐loop transposition of the great arteries. We sought to evaluate these outcomes in patients with bicuspid native pulmonary valve (BNPV). Methods and Results A retrospective analysis of patients with transposition of the great arteries undergoing arterial switch operation at Boston Children's Hospital from 1989 to 2018 matched BNPV patients 1:3 with patients with tricuspid native pulmonary valve by year of arterial switch operation. Kaplan–Meier analyses with log‐rank test compared groups for time to first neo‐aortic valve reoperation, occurrence of ≥moderate AR, and neo‐aortic root dilation (root z score ≥4). A total of 83 patients with BNPV were matched with 217 patients with tricuspid native pulmonary valve. Patients with BNPV more often had ventricular septal defects (73% versus 43%; P<0.001). Hospital length of stay (11 versus 10 days) and 30‐day surgical mortality (3.6% versus 2.8%) were similar. During median 11 years follow‐up, neo‐aortic valve reoperation occurred in 4 patients with BNPV (6.0%) versus 6 patients with tricuspid native pulmonary valve (2.8%), with no significant difference in time to reoperation. More BNPV had AR at discharge (4.9% versus 0%; P=0.014) and during follow‐up (13.4% versus 4.3%; hazard ratio [HR], 3.9; P=0.004), with shorter time to first occurrence of AR; this remained significant after adjusting for ventricular septal defects. Similarly, neo‐aortic root dilation was more common in BNPV (45% versus 38%; HR, 1.64; P=0.026) with shorter time to first occurrence. Conclusions While patients with BNPV have similar short‐term arterial switch operation outcomes, AR and neo‐aortic root dilation occur more frequently and earlier compared with patients with tricuspid native pulmonary valve. Further long‐term studies are needed to determine whether this results in greater need for neo‐aortic valve reoperation.